Case Report: Pediatric acute suppurative thyroiditis caused by Eikenella corrodens: a rare presentation revealing pyriform sinus fistula - Fan Cui; Fan Cui; Lin Zhao; Fanchao Dong; Zhiqiang Yang; Jianjun Dong (Frontiers in Pediatrics)
Acute suppurative thyroiditis (AST) is a rare, potentially life-threatening bacterial infection of the thyroid gland, characterized by rapid progression. We report a rare pediatric case of AST caused by Eikenella corrodens, secondary to a pyriform sinus fistula (PSF), initially misdiagnosed as subacute thyroiditis (SAT). A retrospective analysis highlights the diagnostic challenges and emphasizes the need for early suspicion of PSF in recurrent AST. Timely imaging (CT/laryngoscopy) and pathogen-directed antibiotics are critical to prevent life-threatening complications. This case underscores the importance of considering atypical pathogens and underlying anatomical anomalies in pediatric AST to guide targeted therapy.